The effect of surgeon caseload on the relative revision rate of cemented and cementless unicompartmental knee replacements: An analysis from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man - Mohammad, H; Matharu, G; Judge, A; Murray, D (Lippincott, Williams and Wilkins, 2020)
Background: Unicompartmental knee replacement (UKR) offers substantial benefits compared with total knee replacement (TKR) but is associated with higher revision rates. Data from registries suggest that revision rates for cementless UKR implants are lower than those for cemented implants. It is not known how much of this difference is due to the implant or to other factors, such as a greater proportion of high-volume surgeons using cementless implants. We aimed to determine the effect of surgeon caseload on the revision rate of matched cemented and cementless UKRs.